Water relation response to soil chilling of six olive (Olea europaea L.) cultivars with different frost resistance - Pérez-López, D.; Gijón, M. C.; Mariño, J.; Moriana, A. (Spanish Journal of Agricultural Research, 2010)
The relationship between the water relations of six olive cultivars exposed to different soil temperatures (14 0.1, 9.9 0.1 and 5.8 0.2°C) and their inherent frost resistance (as determined by two different methods) was investigated. Soil chilling was achieved by introducing pots of olive plants into water baths. The water relations of these plants were compared to those of plants kept under conditions of room temperature. The cultivars Frantoio, Picual and Changlot Real began to show significant dehydration below 14°C, while Cornicabra, Arbequina and Ascolana Tenera showed this below 10°C. This response is probably due to delayed stomatal closure. Only Cornicabra and Picual showed a significant reduction in leaf conductance (below 10°C and 6°C respectively). This absence of stomatal control led to a significantly greater dehydration in Ascolana Tenera. These variations in response to the soil chilling temperature suggest that different mechanisms may be at work, and indicate that would be necessary to study the influence of rootstock in the frost resistance of olive plants. The variations recorded grouped the cultivars as either resistant (Cornicabra), tolerant (Picual, Ascolana Tenera and Arbequina), or sensitive (Frantoio and Changlot Real). This classification is in line with the frost resistance reported for these cultivars in the literature, and with the results obtained in the present work using the stomatal density and ion leakage methods of determining such resistance.